Production of 1, 3-propanediol by Clostridium beijerinckii DSM 791 from crude glycerol and corn steep liquor: Process optimization and metabolic engineering. (July 2016) - Wischral, Daiana; Zhang, Jianzhi; Cheng, Chi; Lin, Meng; De Souza, Lucas Monteiro Galotti; Pessoa, Fernando L. Pellegrini; Pereira, Nei; Yang, Shang-Tian
Highlights: C. beijerinckii DSM 791 is a robust organism for 1, 3-PDO production from glycerol. Replacing yeast extract with corn steep liquor increased cell growth and productivity. Stable, long-term 1, 3-PDO production was obtained in repeated batch fermentations. Cell was engineered to overexpress GDH and DHAK. 1, 3-PDO productivity increased 26.8–37.5% with a greatly increased growth rate. Abstract: 1, 3-Propanediol (1, 3-PDO) production from crude glycerol, a byproduct from biodiesel manufacturing, by Clostridium beijerinckii DSM 791 was studied with corn steep liquor as an inexpensive nitrogen source replacing yeast extract in the fermentation medium. A stable, long-term 1, 3-PDO production from glycerol was demonstrated with cells immobilized in a fibrous bed bioreactor operated in a repeated batch mode, which partially circumvented the 1, 3-PDO inhibition problem. The strain was then engineered to overexpress Escherichia coli gldA encoding glycerol dehydrogenase (GDH) and dhaKLM encoding dihydroxyacetone kinase (DHAK), which increased 1, 3-PDO productivity by 26.8–37.5% compared to the wild type, because of greatly increased specific growth rate (0.25–0.40 h −1 vs. 0.13–0.20 h −1 for the wild type). The engineered strain gave a high 1, 3-PDO titer (26.1 g/L), yield (0.55 g/g) and productivity (0.99 g/L·h) in fed-batch fermentation. Overexpressing GDH and DHAK was thus effective in increasing 1, 3-PDO production from glycerol.